Unlock Life - Aram Bartholl (2020)
Beiträge über die Installation: - https://www.monopol-magazin.de/wie-ein-toter-schwan-kurzzeitig-zur-ikone-wurde - https://artinthedigitalage.net/en/2101EN_ann.html - https://www.monopol-magazin.de/aram-bartholl-fossilien-des-spaetkapitalismus?slide=3 - https://taz.de/!5684344/